Regulation Of The Status Of “Ahl Al-Dhimma” and “Ahl Al-Harb” In The Tax System Of Early Arab-Muslim Statehood - Kobil , Zakhidov (Indonesian Journal Publisher, 2024)
The article describes the emergence of the tax system in the Arab caliphate, its spread in the territory of the Arab caliphate and its application to other religions, determining the amount of taxes based on people's financial capabilities, and similar issues.